The Impact of The Tongue Twister Technique on The Speaking Ability of Students and Pronunciation: English - M. Hilmy Hidayatullah; Ukhtul Iffah; Rizqatin Mubarokah ZK (JOEY: Journal of English Ibrahimy, 2025)
The purpose of this study was to gather empirical proof that tongue twisters significantly affect students' speaking abilities and pronunciation. This study employed a quantitative methodology and a quasi-experimental research design. This study was carried out at SMP NAA Alasbuluh-Wongsorejo-Banyuwangi in the eighth grade. The experimental class (38 students) and the control class (41 students) were the two groups in the researcher's basic random sampling technique. The researcher employed a tongue twister test as the tool for data collection, and the students' speaking and pronunciation on the pre-test and post-test were scored using a speaking and pronunciation scoring rubric. The experimental class's post-test mean score, as determined by the t-test calculations, was 80.68, whereas the control class's was 50.65. In the statistical hypothesis test, robserved (0.958) was greater than rtable (0.2213) at the 5% significance level. It indicates that the null hypothesis was rejected and the alternative the hypothesis (Ha) was accepted. It was demonstrated that the tongue twister approach affects eighth-grade students' speaking and pronunciation at SMP NAA Alasbuluh-Banyuwangi